A visualization method for studying the adsorption of lead species in salicylhydroxamic acid flotation of hemimorphite. (1st August 2020) - Zhao, Wenjuan; Liu, Dianwen; Feng, Qicheng
Graphical abstract: Highlights: A novel method for visualizing the adsorption of lead species in SHA flotation of hemimorphite was proposed. ToF-SIMS has the potential to be used for studying adsorption layer of Pb(II) species. SHA could interact with the surface of lead-treated hemimorphite. Pb-SHA complexes formed in solutions could adsorb onto hemimorphite surfaces. Abstract: Salicylhydroxamic acid (SHA) is a selective collector used in the separation of oxide minerals by flotation method, and it is commonly combined with Pb(II) to enhance the floatability of targeted minerals. Due to the limitation of analytical technique, a visualized method to depict the adsorption performance of lead species in the flotation of oxide minerals with SHA as collector was scarce. Time of flight secondary ion mass spectrometry (ToF-SIMS) is a valuable tool for chemical imaging of surfaces and depth profiling. In this work, ToF-SIMS with sputter depth profiling was used to visualize the activation mechanism of Pb(II) in SHA flotation of hemimorphite. Two activation models were proposed and verified. These models involved the adsorption of Pb(II) species onto the hemimorphite surface to improve the reactive sites, thereby enhancing the interaction of SHA. Simultaneously, Pb-SHA complexes in solutions would also adsorb onto the mineral surface, thereby increasing the distribution of lead species.